Chemical and Organoleptic Characteristics of Pineapple Jam Production with Varying Sugar and Pectin Concentrations as Mochi Filling - Wiwik Endah Rahayu; Nurul Mukminah; Fenny Aprilliani (Postgraduate, University of Mataram, 2026)
Pineapple is a key agricultural commodity in Subang Regency. One method of food diversification is transforming pineapple into pineapple jam. Mochi, a food product, can be filled with this pineapple jam. The chemical characteristics and consumer acceptance of pineapple mochi are influenced by the proper ingridients formulation. This study aims to determine the chemical and organoleptic characteristics of pineapple jam as mochi filling. The research design used in this study was a two-factorial Completely Randomized Design (CRD), with the factors being sugar concentration (30%, 40%, and 50%) and pectin concentration (without pectin, 0.015%, and 0.03%). The parameters tested included chemical analysis (water content, total acidity, total soluble solids, and Vitamin C content) and organoleptic evaluation (hedonic test for color, taste, texture, and aroma). The results showed that sugar and pectin treatment had a significant effect on water content G3 21.16b%, total acidity G1 1.90b%, and total soluble solids G3 77.26b%, but did not significantly affect Vitamin C content in the jam 2.20-7.33 m/100 g. Pectin treatment had a significant effect on water content P2 23,27a%, Vitamin C P3 7.09b%, total acidity P3 2.17c%, and total soluble solids P2 76.44b%. There was no interaction between the sugar and pectin treatments on the pineapple mochi jam. The hedonic test indicated that panelists generally liked the pineapple jam filling for mochi in terms of taste, aroma, color, and texture.